The Influence of Work Discipline, Work Skills and Work Motivation on The Performance of Regional Disaster Management Agency Employees Konawe Selatan District” - Farih, Muhammad; Ridwan, Muh.; Handris; Karmila (International Journal of Management and Education in Human Development, 2023)
Management Study Program (S2) Master Program, Faculty of Economics and Business, Halu Oleo University This study aims to examine and explain the simultaneous and partial effects of work discipline, work skills and work motivation on the performance of the employees of the South Konawe District Regional Disaster Management Agency. This research approach is a survey with explanatory research design. The sample of this study were 43 employees of the Konawe Selatan Regency Regional Disaster Management Agency. The data collection method used a questionnaire. The analytical tool used is Multivariate Regression Analysis. The results of the study show that work discipline, work skills and work motivation have a positive and significant effect on the performance of the employees of the South Konawe Regency Regional Disaster Management Agency, both simultaneously and partially. Thus, it can be concluded that work discipline, work skills and work motivation have a positive and significant contribution to improving employee performance as reflected in employee work goals (quantity, quality, time) and work behavior (service orientation, integrity, commitment, work initiative, workequals and leadership).